Learning Project for Improving Principals’ Understanding of Authentic Leadership : A Case Study of Chinese Principals Studying in Finland - Xu, Yuxing (2019)
Having one of the best education (Ruzzi, 2005; Tilastokeskus, 2019), Finland became a popular destination for international education stakeholders. Private and public organizations offer learning projects for international educators, and Tampere University of Applied Sciences (TAMK) is one of them. The study explored the successfulness of an annual learning project for Chinese school principals, offered by TAMK Global Education. Specifically, this qualitative study aims to find out the development of the learning project and of the Chinese principals’ learning. The theoretical framework consists of project-based learning and authentic leadership focusing on the core components. The case study approach is utilized, and interview data from six Chinese principals were analysed with the method of qualitative content analysis. The findings reveal a variety of authentic leadership components in different phases of the learning project. The development of the participants’ understanding of authentic leadership and the progression of the learning project are discussed based on the findings. The study also makes managerial recommendations on learning projects for Chinese educators, which may provide insights to organizations that offer similar activities. The study concludes that the Chinese principals’ understanding of authentic leadership developed as the learning project progresses, and the learning project is successful as it meets various features of a learning project. However, it can still be improved based on the participants’ feedback and multiple research on project-based learning.